Development of nested duplex PCR assays for detection of pathogen Eimeria species in cattle in Papua, Indonesia. Issue 1 (February 2022) - Ekawasti, F; Nashrulloh, M F; Nurcahyo, R W; Priyowidodo, D; Prastowo, J; Firdausy, L W
Abstract: Eimeria bovis and Eimeria zuernii are highly pathogenic Eimeria species in cattle that are the most prevalent causes of a severe clinical illness characterized by hemorrhagic diarrhea in calves and young cattle with potentially fatal effects over the world. The oocysts of a handful of the known bovine eimeriosis species are difficult to distinguish morphologically. For the specific differentiating evidence of Eimeria species, symptomatic research institutions are increasingly relying on DNA-based technologies. This research offers a duplex polymerase chain reaction (PCR) test based on the internal transcribed spacer-1 (ITS-1) gene that may be used to diagnose E. bovis and E. zuernii in cattle from various locations at the same time. The oocysts were concentrated and purified using a fecal harvesting method. The genomic DNA is extracted according to the instructions included with the kit. Primer pairs specific to each species, as well as a standard optimum annealing temperature of 55°C for these species, were discovered. The samples were amplified in a homogenous way, resulting in a homogeneous band ladder, revealing that the test could distinguish between two highly pathogenic Eimeria species in one tube reaction. This duplex PCR assay can detect a high pathogenic bovine Eimeria simultaneously in a rapid and low cost.